2021
DOI: 10.1186/s12891-021-04817-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of functional outcomes between OTA/AO type C, Gustilo type I/II open fractures and closed fractures of the distal humerus treated by open reduction and internal fixation

Abstract: Background To evaluate the difference of functional outcomes between OTA/AO type C, Gustilo type I/II open fractures and closed fractures of the distal humerus after open reduction and internal fixation. Methods We retrospectively analyzed the clinical data of patients with OTA/AO-C distal humerus fractures who were treated in our department from January 2014 to December 2016. The patients were divided into an open fracture group and a closed fract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The most widely used plate fixation method is placing plates perpendicular to each other one over medial supracondylar ridge and other one over the flat posterior surface of lateral column called as orthogonal plating. Stoffel et al demonstrated on mechanical studies two plates placed parallel to each other, one over each supracondylar ridge, providing better stability in compression and external rotation than to perpendicular plating system in cadaveric models (15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used plate fixation method is placing plates perpendicular to each other one over medial supracondylar ridge and other one over the flat posterior surface of lateral column called as orthogonal plating. Stoffel et al demonstrated on mechanical studies two plates placed parallel to each other, one over each supracondylar ridge, providing better stability in compression and external rotation than to perpendicular plating system in cadaveric models (15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%